dbs Summer School Klinische Linguistik 2024. Sprachtherapie bei Kindern und Jugendlichen mit Schädel-Hirn-Trauma - Rosenkranz, A.; Kuhles, G.; Falkowska, Z.; Jaecks, P.; von Lehmden, F.; Büttner-Kunert, J.; Jonas, Kristina (Sprachtherapie aktuell: Forschung – Wissen – Transfer 13(1). dbs Summer School Klinische Linguistik)

The Co-CALIBRATE Framework: An Evidence-Based Framework for the Cultural Adaptation of Brain Injury Intervention Tools with Stakeholder Engagement. - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, B.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L.

Das Co-CALIBRATE Framework: Ein international konsentiertes, evidenzbasiertes Framework für kultur-sensitive Adaptationen von Therapie-Ressourcen im Bereich Sprach- und Kommunikationsstörungen nach Hirnschädigungen - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (Jahrestagung der Gesellschaft für Aphasieforschung und -behandlung (GAB) e.V., Aachen.)

Co-CALIBRATE: An Evidence-Based Framework For The Cultural Adaptation of Brain Injury Intervention Tools With Stakeholder Engagement - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (15. World Congress on Brain Injury, Montreal, Canada)

'Co-CALIBRATE: Developing a Culturally Sensitive Framework for Adapting ABI Interventions in Diverse Population - Avramovic, P.; Quinting, J.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (4th CCD Symposium, Coventry, UK.)

Status quo of clinical use and scientific value of quality of life and neurocognitive assessment practice in neuro-oncological patients

Category naming for intraoperative monitoring of contextual association

Digital participation of brain tumour patients in the assessment and treatment of communication disorders - Weiss Lucas, C; Kochs, S; Jost, J; Loução, R; Kocher, M; Goldbrunner, R; Wiewrodt, D; Jonas, Kristina (Frontiers in. Psychology)

Editorial: Digital participation and communication disorders across the lifespan - Jonas, Kristina; Jaecks, P; Frieg, H (Frontiers in. Psychology)

Kurzfassung und interdisziplinäre Kommentierung der internationalen INCOG-2.0-Leitlinie „Kognitive Kommunikationsstörungen nach Schädelhirntrauma“ - Thoma, Patrizia; Quinting, Jana; Jonas, Kristina; Regenbrecht, Frank; Schumacher, Rahel; Büttner-Kunert, Julia (Zeitschrift für Neuropsychologie)
Zusammenfassung: Kognitive Kommunikationsstörungen (Cognitive Communication Disorders = CCDs) bezeichnen kommunikative Beeinträchtigungen, die v. a. die kommunikativ-pragmatischen Fähigkeiten betreffen und primär durch begleitende kognitive Störungen, z. B. der Gedächtnis-, Aufmerksamkeits-, und exekutiven Planungsfunktionen bedingt sind. Eine besondere Rolle spielen außerdem Beeinträchtigungen Sozialer Kognition (z. B. Empathie, Theory of Mind). Somit fällt die Diagnostik und Behandlung der CCDs interdisziplinär in den Zuständigkeitsbereich der Klinischen Neuropsychologie und der Sprachtherapie. Ein internationales, interdisziplinäres Netzwerk, die sog. INCOG-Arbeitsgruppe, hat im Jahre 2023 aktualisierte, evidenzbasierte Empfehlungen zur Diagnostik und Behandlung von CCDs und begleitender soziokognitiver Störungen spezifisch nach mittelschweren bis schweren Schädel-Hirn-Traumata veröffentlicht. Diese sollen im vorliegenden Artikel zusammenfassend vorgestellt und kommentiert werden. Es werden erste Vorschläge zur konkreten interdisziplinären Zusammenarbeit von Klinischer Neuropsychologie und Sprachtherapie abgeleitet.

A systematic approach to neurocognitive assessment for better detection and prevention of deficits in surgically treated brain tumours - Lucas, Carolin Weiß; Rodrian, Kimberley; Kochs, Sophia; Schultze-Rhonhof, Mira; Schroeter, Catharina; Becker, Maura; Nettekoven, Charlotte; Loução, Ricardo; Pieczewski, Julia; Jonas, Kristina; Kocher, Martin; Wiewrodt, Dorothee; et al. (Brain and Spine)

Ultra-short train TMS for more specific mapping of cortical language areas

Kognitive Kommunikationsstörungen in der Neurorehabilitation – Herausforderungen und Chancen in Versorgung und Modelltheorie

Diagnostik Subtiler Kognitiver Kommunikationsstörungen nach Schädel-Hirn-Trauma - Quinting, J.; Stenneken, P.; Rubi-Fessen, I.; Jonas, Kristina (Forum Logopädie)

Syntactic priming in sentence comprehension in aphasia - Jaecks, P; Jonas, Kristina (Aphasie und verwandte Gebiete)

Kommunikation – Sprache, Emotion, Kognition

Measuring Verbal Reasoning and Executive Strategies in German Speaking People with Cognitive-Communication Disorders: Cross-Cultural Adaptation and Pilot Testing of the FAVRES-DE - Quinting, Jana; Stenneken, Prisca; Mahlke, Anne; de Beer, Carola; Hogrefe, Katharina; Hussmann, Katja; Baumgaertner, A.; MacDonald, Sheila; Jonas, Kristina (Aphasiology)

Zusammenspiel sprachlicher und kognitiver Funktionen in der Diagnostik beeinträchtigter Kommunikationsfähigkeit bei Kindern und Jugendlichen - Jonas, Kristina; Stenneken, P (Handbuch der sonderpädagogischen Diagnostik. Grundlagen und Konzepte der Statusdiagnostik, Prozessdiagnostik und Förderplanung)

Emotion Recognition, Empathy or ToM? Influence of Social Cognition Subcomponents on Communicative Competence in Individuals with Traumatic Brain Injury – A Systematic Review - Quinting, J; Jonas, Kristina; Kuhn, C; Stenneken, P (Zeitschrift für Neuropsychologie)

Characteristics of language and communication after subcortical lesions in the left and right hemisphere